A Rare Cause of Acute Myocardial Infarction: Coronary Artery Embolism - Demırellı, Selami; Arslan, Sakir; Bakırcı, Eftal Murat; Arısoy, Arif; Degırmencı, Husnu (Fırat University, 2012)
A 49-year-old woman with a history of hypertension, diabetes mellitus and aortic valve replacement five years ago, admitted to our outpatient clinic with shortness of breath. Transesophageal echocardiography revealed a 5x2 mm thrombus on the anterior face of prosthetic aortic valve. A throm-bolytic therapy (TT) was initiated but it was unsuccessful. In the tenth day of follow-up, she experienced chest pain with ST segment elevations through V2-V6 derivations on her ECG. With the diagnosis of acute myocardial infarction, the patient was taken into the catheterization laboratory. In the coronary angiography, the mid segment of left anterior descending artery was completely occluded by a thrombus. Percutaneous transluminal coronary angioplasty was performed but it was failed. After then TT was started again. The second TT has become successful both in terms of coronary revascularization and resolusion of valve thrombosis.

Beş yıl önce aort kapak replasmanı yapılan, diyabet ve hipertansiyon hikayesi olan, kırk dokuz yaşındaki bayan hasta kliniğimize nefes darlığı şikayeti ile başvurdu. Transözefajial ekokardiyografide aortik protez kapağın ön yüzünde 5Ã—2 mm trombüs ile uyumlu görüntü izlendi. Trombolitik tedavi uygulandı ancak başarısız olundu. Takibin onuncu gününde hastada göğüs ağrısı ile birlikte EKG'de V2-V6 derivasyonlarında ST segment elevasyonu gözlendi. Akut miyokard infarktüsü tanısı ile yapılan koroner anjiyografide, sol inen arter orta segment trombüs ile tıkalıydı. Perkütan translüminal koroner anjiyoplasti denendi ancak başarısız olundu. Hastaya ikinci kez trombolitik tedavi uygulandı. İkinci kez uygulanan trombolitik tedavinin, hem koroner revaskülarizasyon hem de kapak trombozu açısından başarılı olduğu gözlendi.
Akut Miyokard İnfarktüsünün Nadir Bir Nedeni: Koroner Arter Embolisi